DISCOVERY LEARNING MODEL AS A SOLUTION TO DEVELOP STUDENTS' UNDERSTANDING IN MATRIX CONCEPT - Sri Nadia Khairunnisa; Harry Dwi Putra; Eka Senjayawati (Universitas Islam Negeri Alauddin Makassar, 2020)
Abstract: This study aims to examine the increasing mastery of the concept of the matrix through the Discovery Learning model. This research is a class action research. The subjects in this study were students of Class XI TEDK-A at SMK Negeri 1 Cimahi. Data sources are teachers and students. Data collection techniques using tests and observation sheets. Based on data analysis, the average of student learning outcomes has increased by 77.42, from the first test cycle achieved by 10.00 to the last testing cycle achieved by 87.42. From the results, it can be concluded that there is an improvement in students' mathematical understanding of the matrix material in class XI TEDK-A in SMK Negeri 1 Cimahi students who use the discovery learning model.   Abstrak: Penelitian ini bertujuan untuk menguji apakah penguasaan konsep matriks melalui model Discovery Learning dapat ditingkatkan. Jenis penelitian ini adalah penelitian tindakan kelas. Subjek dalam penelitian ini adalah siswa kelas XI TEDK-A di SMK Negeri 1 Cimahi. Sumber data diperoleh dari guru dan siswa. Teknik pengumpulan data menggunakan tes dan lembar observasi. Berdasarkan analisis data, rata-rata hasil belajar siswa meningkat sebesar 77,42 dari siklus tes pertama yang dicapai sebesar 10,00 hingga siklus pengujian terakhir yang dicapai oleh 87,42. Dari hasil penelitian dapat disimpulkan bahwa terdapat peningkatan pemahaman matematis siswa pada materi matriks siswa kelas XI TEDK-A di SMK Negeri 1 Cimahi dengan menggunakan model Discovery Learning.